Budaya populer dan identitas nasional: pengaruh budaya Korea dalam gobalisasi pada generasi muda di indonesia - patikah, patikah02 (Maliki Interdisciplinary Journal, 2025)
The era of globalisation today is a huge challenge, globalisation has spread through mass media such as social media, video content on the internet, or blogs on the internet or even entertainment media as well as technology making a very significant impact on the national identity of the younger generation. Viewed from various sides, on the one hand this is the first step of the opportunity to open cross-cultural and introduction of local culture but on the other hand it can cause erosion of cultural values, commercial culture adds, and causes an identity crisis in the younger generation. This article will discuss the influence of global culture on traditional values, as well as how the younger generation moves between the preservation of national identity and openness to global culture. The younger generation generally only wants to think about pleasure, which means they are easily influenced by other things that they have to follow. This article will discuss about. Various cultures produced from Pop culture or Korean culture, namely in terms of music, drama, fashion, electronic devices, to beauty products (make up and skincare).